Floating-Point ALU Design - Huang, Seow Ling (2003)
This project presents a floating-point arithmetic unit using pipelining concept. The arithmetic unit constructed supports the four primitive operations of computer arithmetic namely addition, subtraction, multiplication and divison based on IEEE-754 standard.